2013
DOI: 10.13054/mije.13.18.3.2
|View full text |Cite
|
Sign up to set email alerts
|

Experience of Elementary School Students with the Use of WebQuests

Abstract: The aim of this study was to examine the perspectives of primary school students on the use of WebQuests in learning. There were nine graduate students, twenty-six 4th grade and thirty 5th grade pupils involved in this study, which took place over eight weeks in a graduate course. The graduate students designed and developed their WebQuests as a project based on their interests. The researcher gave a questionnaire, including open-ended questions, to both graduate students and primary school students, who state… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
0
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 22 publications
2
0
0
1
Order By: Relevance
“…Concerning technology use, the finding of the current study implied that using technology in teaching English can promote students' motivation. This finding mirrors the results of previous research (Godzicki et al, 2013;Halat, 2013;Heafner, 2004). Therefore, it is recommended to use technology because students become actively engaged and motivated when technology is used appropriately in English classrooms.…”
Section: Discussionsupporting
confidence: 92%
“…Concerning technology use, the finding of the current study implied that using technology in teaching English can promote students' motivation. This finding mirrors the results of previous research (Godzicki et al, 2013;Halat, 2013;Heafner, 2004). Therefore, it is recommended to use technology because students become actively engaged and motivated when technology is used appropriately in English classrooms.…”
Section: Discussionsupporting
confidence: 92%
“…The results of the present study suggested that employing technology to teach English can increase students' motivation. This discovery is consistent with earlier study findings (Godzicki et al, 2013;Halat, 2013;Heafner, 2004). Hence, it is advised to employ technical inventions since, when it is used properly in English classrooms, pupils become actively engaged and motivated.…”
Section: International Journal Of Research In Social Sciences and Hum...supporting
confidence: 94%
“…Karena media google sites merupakan teknologi yang sering dijumpai guru saat mengoperasikan teknologi digital berbasis web. Selain itu menurut Halat (2013) aktivitas web merupakan salah satu penggunaan yang dapat dipelajari dengan cepat dibandingkan dengan sosial media. Alasan yang mendasari pemilihan media berbasis web, karena terbukti berpotensi membantu setiap permasalahan dalam pembelajaran, khususnya dalam materi matematika sebagai meningkatan kemampuan numerasi (Tsekleves, Cosmas, and Aggoun 2016).…”
Section: Pendahuluanunclassified